ANGKA BANDING ALBUMIN KREATININ AIR KEMIH DAN HbA1C SERTA ESTIMASI LAJU FILTRASI GLOMERULUS PADA PASIEN DIABETES MELITUS TIPE 2 (Urinary Albumin to Creatinine Ratio With HbA1c and Estimated Glomerulo Filtration Rate in Type 2 Diabetes Mellitus Patients) - Amiroh Kurniati; Tahono Tahono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Diabetes Mellitus (DM) type 2 is a metabolic disease that prevalence increasing. A chronic hyperglycemia with poor glycemiccontrol can stimulate oxidative stress, which will continue to occurrence of complications in the kidneys characterized by the presenceof microalbuminuria can be measured by the ratio of urinary albumin creatinine ratio (UACR) and the change in estimated glomerularfiltration rate (eGFR). The aims of this study was to know the correlation between the UACR with HbA1c value and eGFR in patients withtype 2 DM by finding them out. This study used cross sectional research design. Subjects were patients with type 2 DM who attend controlin Endocrinology Subdivision of Internal Medicine Departement and perform blood and urine tests in Clinical Pathology Laboratory inDr. Moewardi Hospital Surakarta in August 2013. To determine the pattern of the data distribution, the researchers used KolmogorovSmirnov test, and to analyse the result used Spearman (r) correlation with p<0.05 and confidence interval 95%. Statistical analysisusing Spearman correlation test (r), significant when p<0.05 with 95% confidence intervals. From 68 samples examined the meanage is 60.9 year old, with equal participants for male and female (34 subjects each). Most subjects were in poor glycemic control group(72.1%) and in the range of microalbuminuria (44.1%). There was a significant correlation between UACR with HbA1c and eGFR intype 2 DM patient (r=0.412, p=0.000; and r= -0.270, p=0.02, respectively). Based on this study it can be concluded that increasedUACR were associated with worsened glycemic control and were characterized by higher levels of HbA1c and its eGFR value would belower. Further analysis requires further research with a larger sample size and more attention to the factors that may affect the relatedexamination.